Examination of the effects of virus inactivation methods on the induction of antibody- and cell-mediated immune responses against whole inactivated H9N2 avian influenza virus vaccines in chickens - Astill, Jake; Alkie, Tamiru; Yitbarek, Alexander; Taha-Abdelaziz, Khaled; Bavananthasivam, Jegarubee; Nagy, Éva; Petrik, James John; Sharif, Shayan (Vaccine, 2018)
•Inactivating influenza viruses can alter their structure and function.•Structural changes of inactivated influenza viruses affect vaccine immune responses.•Beta-propiolactone, formaldehyde, and gamma radiation can be used for inactivation.•Beta-propiolactone inactivated H9N2 virus enhanced immune responses in chickens. Several types of avian influenza virus (AIV) vaccines exist, including live-attenuated, vectored, and whole inactivated virus (WIV) vaccines. Inactivated vaccines offer some advantages compared to other types of vaccines, including ease of production and lack of ability to revert to a virulent state. However, WIV are poorly immunogenic, especially when these vaccines are delivered to mucosal surfaces. There are several factors that contribute to the immunogenicity of vaccines, one of which is the method used to inactivate viruses. Several methods exist for producing influenza WIVs, including formaldehyde, a chemical that affects protein structures leading to virus inactivation. Other methods include treatment with beta-propiolactone (BPL) and the application of gamma radiation, both of which have less effects on protein structures compared to formaldehyde, and instead alter nucleic acids in the virion. Here, we sought to determine the effect of the above inactivation methods on immunogenicity of AIV vaccines. To this end, chickens were vaccinated with three different H9N2 WIVs using formaldehyde, BPL, and gamma radiation for inactivation. In addition to administering these three WIVs alone as vaccines, we also included CpG ODN 2007, a synthetic ligand recognized by Toll-like receptor (TLR)21 in chickens, as an adjuvant for each WIV. Subsequently, antibody- and cell-mediated immune responses were measured following vaccination. Antibody-mediated immune responses were increased in chickens that received the BPL and Gamma WIVs compared to the formaldehyde WIV. CpG ODN 2007 was found to significantly increase antibody responses for each WIV compared to WIV alone. Furthermore, we observed the presence of cell-mediated immune responses in chickens that received the BPL WIV combined with CpG ODN 2007. Based on these results, the BPL WIV + CpG ODN 2007 combination was the most effective vaccine at inducing adaptive immune responses against H9N2 AIV. Future studies should characterize mucosal adaptive immune responses to these vaccines.